Breastfeeding and decreased risk for childhood obesity - Aspri Sulanto; Setya Wandita; Madarina Julia (Paediatrica Indonesiana, 2012)
Background Breast milk promotes infant growth and appropriateweight gain, minimizing the risk for malnutrition, and possiblyfor obesity.Objective To determine the influence of infant breastfeedingpractices on the risk for obesity in children aged 6 to 8 years.Methods We conducted a case-control study comparingbreastfeeding practices between obese and non-obese children.Subjects were selected from two elementary schools in Yogyakarta.Case subjects had body mass index (BMI)-for-age <::: + 2 SD(WHO 2007 growth reference curve). Control subjects had BMIfor-age SD between-2and+1 SD, and were matched for age andgender to the case subjects. Subjects' mothers filled questionnaireson their breastfeeding practices.Results We recruited 68 pairs of obese and non-obese subjects,4 7 (69%) pairs of boys and 21 (31 %) pairs of girls. The meanduration of breastfeeding in the obese group was shorter thanthat of the non-obese group, 12.9 months (SD 9.78) vs. 16.1months (8.39), respectively, a mean difference of 3.24 months(95% CI 0.14 to 6.32). Partially breastfed and formula-fed childrenhad significantly higher odds for obesity compared to that ofexclusively breastfed children, OR4.70 (95% CI 3.96 to 5.43) forpartial breastfeeding and 6.20 (95% CI 4.67 to 7.73) for formulafeeding. The risk for obesity also declined with longer durationsof breastfeeding.Conclusion Exclusive infant breastfeeding and longer durationof breastfeeding lowered the risk for childhood obesity in childrenaged 6-8 years. [Paediatr lndones. 2012;52: 1-5].Â